Sequencing, Physiological Regulation, and Representative Disease Research Progress of RNA m6A Modification - Xiaoqian Chen; Yuanyuan Li; Youfang Gan; Yuyang Guo; Hongling Zhou; Rui Wang (Georg Thieme Verlag KG, 2024)
To date, more than 150 chemical modifications have been disclosed in different RNA species, which are employed to diversify the structure and function of RNA in living organisms. The N 6-methyladenosine (m6A) modification, which is found in the adenosine N 6 site of RNA, has been demonstrated to be the most heavy modification in the mRNA in cells. Moreover, the m6A modification in mRNAs of mammalian and other eukaryotic cells is highly conserved and mandatorily encoded. Increasing evidence indicates that the m6A modification plays a pivotal role in gene-expression regulation and cell-fate decisions. Here, we summarize the most recent m6A-sequencing technology, as well as the molecular mechanism underlying its occurrence, development, and potential use as a target for the treatment of human diseases. Furthermore, our review highlights other newly discovered chemical modifications of RNA that are associated with human disease, as well as their underlying molecular mechanisms. Thus, significant advancements have been made in qualitative/quantitative m6A detection and high-throughput sequencing, and research linking this RNA modification to disease. Efforts toward simplified and more accessible chemical/biological technologies that contribute to precision medicine are ongoing, to benefit society and patients alike.